The role of compensation of carbohydrate metabolism in pregnant women with type 1 diabetes mellitus in the development of perinatal complications - Roza Mikhailovna Esayan; Olga Rafael'evna Grigoryan; Elena Vladimirovna Pekareva (Сахарный диабет)
With DM1 morbidity reaching epidemic growth in young people including women of childbearing age, planning and managing pregnancy in patientswith disturbances of carbohydrate metabolism acquires increasingly greater significance. Of primary importance are evening mutual influence of DM1and pregnancy (a high-risk condition) and prevention of perinatal complications resulting from poor compensation of carbohydrate metabolism.